2001
DOI: 10.1088/1126-6708/2001/06/058
|View full text |Cite
|
Sign up to set email alerts
|

Confining strings and RG flow in the (2+1)-dimensional Georgi-Glashow model and its SU(3)-generalization

Abstract: Confining strings and RG flow at finite temperature are investigated in the (2+1)-dimensional Georgi-Glashow model. This is done in the limit when the electric coupling constant is much larger than the square root of mass of the Higgs field, but much smaller than the vacuum expectation value of this field. The modification of the Debye mass of the dual photon with respect to the case when it is considered to be negligibly small compared to the Higgs mass, is found. Analogous modifications of the potential of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
28
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…[6], the influence of the Higgs field to the dynamics of the Georgi-Glashow model has been studied both at zero and nonzero temperature. In particular, it has been found that the finiteness of the Higgs-boson mass does not change the value of the critical temperature of the monopole BKT phase transition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6], the influence of the Higgs field to the dynamics of the Georgi-Glashow model has been studied both at zero and nonzero temperature. In particular, it has been found that the finiteness of the Higgs-boson mass does not change the value of the critical temperature of the monopole BKT phase transition.…”
mentioning
confidence: 99%
“…However, in ref. [6] the effects of W-bosons have been disregarded, that makes the performed analysis incomplete. The aim of the present letter is to explore the influence of the Higgs-mediated interaction of monopoles to the deconfining phase transition with the account for W-bosons.…”
mentioning
confidence: 99%
“…Besides the investigations performed in the compact-QED limit of this model (where the Higgs boson is infinitely heavy), there have recently also been done several investigations of the Georgi-Glashow model beyond that limit [2,3]. The analysis of ref.…”
mentioning
confidence: 99%
“…The analysis of ref. [2] has been carried out in the Bogomolny-Prasad-Sommerfield (BPS) limit [4], that is the limit where the Higgs field is much lighter than the W-boson. In that paper, the theory has been investigated both at zero and nonzero temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation